Breast Cancer Statistics, 2022. (3rd October 2022) - Giaquinto, Angela N.; Sung, Hyuna; Miller, Kimberly D.; Kramer, Joan L.; Newman, Lisa A.; Minihan, Adair; Jemal, Ahmedin; Siegel, Rebecca L.
Abstract: This article is the American Cancer Society's update on female breast cancer statistics in the United States, including population‐based data on incidence, mortality, survival, and mammography screening. Breast cancer incidence rates have risen in most of the past four decades; during the most recent data years (2010–2019), the rate increased by 0.5% annually, largely driven by localized‐stage and hormone receptor‐positive disease. In contrast, breast cancer mortality rates have declined steadily since their peak in 1989, albeit at a slower pace in recent years (1.3% annually from 2011 to 2020) than in the previous decade (1.9% annually from 2002 to 2011). In total, the death rate dropped by 43% during 1989–2020, translating to 460, 000 fewer breast cancer deaths during that time. The death rate declined similarly for women of all racial/ethnic groups except American Indians/Alaska Natives, among whom the rates were stable. However, despite a lower incidence rate in Black versus White women (127.8 vs. 133.7 per 100, 000), the racial disparity in breast cancer mortality remained unwavering, with the death rate 40% higher in Black women overall (27.6 vs. 19.7 deaths per 100, 000 in 2016–2020) and two‐fold higher among adult women younger than 50 years (12.1 vs. 6.5 deaths per 100, 000). Black women have the lowest 5‐year relative survival of any racial/ethnic group for every molecular subtype and stage of disease (except stage I), with the largest Black–White gaps in absolute terms for hormone receptor‐positive/human epidermal growth factor receptor 2‐negative disease (88% vs. 96%), hormone receptor‐negative/human epidermal growth factor receptor 2‐positive disease (78% vs. 86%), and stage III disease (64% vs. 77%). Progress against breast cancer mortality could be accelerated by mitigating racial disparities through increased access to high‐quality screening and treatment via nationwide Medicaid expansion and partnerships between community stakeholders, advocacy organizations, and health systems.